Pengaruh Perilaku Keuangan, Pendapatan, Gaya Hidup Terhadap Minat Investasi Emas Sales Marketing Di Toko Mas Jawa Area Solo - Putri Retno Yuliasari; Ari Susanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The movement of gold prices, which has continued to increase over the past year, is one of the backgrounds for this research. This research aims to determine the influence of financial behavior, income and lifestyle on gold investment decisions in the sales marketing of Toko Mas Jawa Solo Area. This research uses a quantitative approach by distributing questionnaires with a sample of 71 respondents, obtained using a saturated sampling technique. Research data was processed using SPSS, where hypothesis testing was analyzed using the t test and multiple linear regression analysis.